2019
DOI: 10.1021/acsomega.9b01073
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Surface-Enhanced Raman Spectroscopy for Cholesterol-Modified Lipid Systems: Effect of Gold Nanoparticle Size

Abstract: A gold nanoparticle (AuNP) has a localized surface plasmon resonance peak depending on its size, which is often utilized for surface-enhanced Raman scattering (SERS). To obtain information on the cholesterol (Chol)-incorporated lipid membranes by SERS, AuNPs (5, 100 nm) were first functionalized by 1-octanethiol and then modified by lipids (AuNP@lipid). In membrane surface-enhanced Raman spectroscopy (MSERS), both signals from 1,2-dioleoyl- sn -glycero-3-phosphocholine (DOPC) and Chol mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 51 publications
2
16
0
Order By: Relevance
“…Small particles influenced the lipid fluidity and polarity of the membranes by weakening hydrophobic interactions between lipids' molecules. However, overall the effect was not significant and it was concluded that embedding of the particles into the lipid bilayer does not disturb the membrane properties, which is also supported by their previous observation for DOPC/CH liposomes [82].…”
Section: Ramansupporting
confidence: 75%
See 1 more Smart Citation
“…Small particles influenced the lipid fluidity and polarity of the membranes by weakening hydrophobic interactions between lipids' molecules. However, overall the effect was not significant and it was concluded that embedding of the particles into the lipid bilayer does not disturb the membrane properties, which is also supported by their previous observation for DOPC/CH liposomes [82].…”
Section: Ramansupporting
confidence: 75%
“…However, the descriptor, e.g. 'gold nanoparticle' is misleading as the metallic centre invariably has another ion, such as citrate, or, any other purpose-specific functionalisation [82] on the surface of the metal core. The surface-functionalisation [83] as well as particle size [84] and shape [85] influence the membrane-particle interaction and should be considered.…”
Section: Ramanmentioning
confidence: 99%
“…Increasing cholesterol leads to a decrease in membrane fluidity [ 42 , 43 ] and changes in the erythrocyte function [ 44 ]. The SERS ratio I 2872 /I 2927 was proposed as a marker of cholesterol amount by Faried et al [ 45 ]. Thus, an increase in this ratio, indicating an increase in the membrane stiffness, may be explained by an increased amount of cholesterol in the erythrocyte plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“… 113 When the gold nanoparticles are small enough to fit the intralamellar space of liposomes, an octanethiol functionalization can direct them there, and they selectively enhance signals due to vibrations of the acyl chains. 112 Cetyltrimethylammonium bromide (CTAB), a typical surfactant used in the synthesis of gold nanorods, can be displaced from the nanostructures’ surface by lipids, and a lipid bilayer can form around such particles without the need of further functionalization. 114 SERS spectra reveal the dynamics of these membrane structures and indicate that lipid exchange occurs between the bilayer around the nanoparticles and vesicles contained in the same solution.…”
Section: Sers Of Molecular Models Improves Our Understanding Of Intra...mentioning
confidence: 99%